Diagnostic Utility of HPV16 E6 mRNA or E7 mRNA Quantitative Expression for Cervical Cells of Patients with Dysplasia and Carcinoma. Issue 9 (September 2018) - Wu, Ming-Zhe; Li, Wei-Nan; Cha, Na; Tian, Li-Xiang; Zhang, YI; Wu, Xin; Guo, Ke-Jun; Wu, Guang-Ping
Current human papillomavirus (HPV)16 DNA testing has high sensitivity but low specificity, while mRNA testing (qualitative) improves the specificity. However, both techniques are not able to discriminate between transient and persistent infections. To overcome the disadvantages, we quantitatively detected E6 and E7 mRNAs by quantitative real-time polymerase chain reaction (qRT-PCR) in cervical brushing cells from 87 HPV16+ and 31 HPV16− patients. Our results showed that the expression levels of E6 mRNA or E7 mRNA were significantly increased in HPV16-positive cases than that in the negative cases. Furthermore, in HPV16+ cases, the expression levels of E6 mRNA were significantly increased in invasive cancer compared with high-grade squamous intraepithelial lesion (HSIL; p < 0.01), and HSIL compared with low-grade squamous intraepithelial lesion (LSIL; p < 0.01). There were no significant changes between LSIL and benign lesions. The expression levels of E7 mRNA presented no significant difference among the above-mentioned four groups. To test whether qRT-PCR can discriminate between transient and persistent infections, 57 HPV16+ patients were followed up for 1 year, and our results demonstrated that the expression levels of both E6 mRNA and E7 mRNA in the persistent infection group were significantly increased relative to the transient infection group ( p < 0.01 or 0.05). Thus, a quantitative detection of the expression levels of E6 mRNA in cervical brushing cells may not only be used as an ancillary tool to cytological diagnosis of cervical neoplasia, but may also help to determine the severity of the lesions and the triage of transient infection.